2013
DOI: 10.1109/jstqe.2012.2235824
|View full text |Cite
|
Sign up to set email alerts
|

Concentric Ring Structures as Efficient SERS Substrates

Abstract: Plasmonic nanopatterned structures that can work as highly efficient surface-enhanced Raman scattering (SERS) substrates are presented in this study. A "coupled" concentric ring structure has been designed, fabricated, tuned, and compared to an "etched" concentric ring structure and plain gold film via SERS experiments. The proposed design gives Raman signal intensity 630 times larger than plain gold film and 8 times larger than an "etched" concentric ring structure. The surface plasmons were imaged with the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…The SERS enhancement predicted through simulations and measured via SERS experiments have shown that the tandem nano-cone design provided 10 times higher SER signal intensity when compared with periodic Au nano-cone arrays fabricated with the same method. The enhancement would be more prominent if the comparison was made with respect to simply nano-roughened metallic surfaces, as shown in another study conducted by the Ozbay group [24].…”
Section: Tandem Structuresmentioning
confidence: 79%
See 2 more Smart Citations
“…The SERS enhancement predicted through simulations and measured via SERS experiments have shown that the tandem nano-cone design provided 10 times higher SER signal intensity when compared with periodic Au nano-cone arrays fabricated with the same method. The enhancement would be more prominent if the comparison was made with respect to simply nano-roughened metallic surfaces, as shown in another study conducted by the Ozbay group [24].…”
Section: Tandem Structuresmentioning
confidence: 79%
“…Concentric arcs and rings are used for various purposes in the literature mainly for their focusing properties [25] or as plasmonic lenses [26]. In our study, circular concentric rings etched from a planar gold film are compared with their coupled counterparts and plain gold film in terms of their SERS performance [24]. In the coupled design, the etched parts are filled with a dielectric and then layered up with gold circular concentric rings as shown in the inset of Fig.…”
Section: Concentric Ring Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to elevated NAs, also arrays of plasmonic nanopillars have been considered for SERS sensing, since this configuration reduces the interference of the electromagnetic field with the substrate and provides, at the same time, a tridimensional sensing environment [240,241]. Also structures without sharp edges have shown satisfactory results in terms of both EF and LOD; in particular, metallic concentric rings have been considered due to their capability to focus light, allowing therefore to obtain a high spatial control over SERS signal intensity [242,243]. Finally, even though periodic arrangements of metallic NAs constitute the most employed substrates for SERS sensing, they are not the unique possibility.…”
Section: Sers Experimentsmentioning
confidence: 99%
“…Controlling the SERS signal via patterned metallic nanostructures and arrays has been an attractive research area in recent years. There are several examples where the nanostructures with different geometries, shapes, and sizes have been used as SERS substrates [12][13][14][15]. As a rule of thumb, an optimal substrate should provide the highest possible average field enhancement at the metal molecule interface.…”
Section: Introductionmentioning
confidence: 99%